2013
DOI: 10.1165/rcmb.2013-0074oc
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of Lipopolysaccharide into Mice with Emphysema Mimics Human Chronic Obstructive Pulmonary Disease Exacerbation as Assessed by Micro-Computed Tomography

Abstract: Chronic obstructive pulmonary disease (COPD), manifested as emphysema and chronic airway obstruction, can be exacerbated by bacterial and viral infections. Although the frequency of exacerbations increases as the disease progresses, the mechanisms underlying this phenomenon are largely unknown, and there is a need for a simple in vivo exacerbation model. In this study, we compared four groups of mice treated with PBS alone, elastase alone, LPS alone, and elastase plus LPS. A single intratracheal administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
65
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 35 publications
10
65
1
Order By: Relevance
“…preceded the significant increase of DI in CS-exposed mice might be that the increase of end-expiratory lung volume on micro-CT reflects the structural narrowing and/or functional resistance of small airways that could be overlooked by artificial inflation of lungs with fixative for evaluation techniques used in histopathology. Elastase-treated mice also displayed a high expiratory total lung volume, as was previously reported (7,14), but it is due to the increase of low-density volume, which is in sharp contrast to the CS exposure model.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…preceded the significant increase of DI in CS-exposed mice might be that the increase of end-expiratory lung volume on micro-CT reflects the structural narrowing and/or functional resistance of small airways that could be overlooked by artificial inflation of lungs with fixative for evaluation techniques used in histopathology. Elastase-treated mice also displayed a high expiratory total lung volume, as was previously reported (7,14), but it is due to the increase of low-density volume, which is in sharp contrast to the CS exposure model.…”
Section: Discussionsupporting
confidence: 70%
“…Micro-CTbased protocols for the quantification of a variety of pulmonary emphysema models in mice have been proposed, and agreement with current gold standard evaluation of histopathology has been reported (2,8,21). We also have recently reported the use of micro-CT to monitor the progression of emphysematous changes in an exacerbation mouse model of COPD by a single administration of elastase followed by lipopolysaccharide (14). Different parameters are used to quantify the extent of the emphysematous disease, such as the mean CT density, identification of low-density areas (i.e., LAA) using a variety of thresholds, and %LAA.…”
mentioning
confidence: 53%
“…The frequency distribution revealed that low CT values were the most pronounced in the Mfap4 Ϫ/Ϫ mice. Areas of lower than Ϫ600 HUs, which were recognized as low-density areas (LAA%), were significantly increased as previously described in emphysematous lungs of murine models (12,21,24,33). The low-density areas in the whole lungs of the wild-type mice were mainly restricted to the airways, whereas the corresponding areas in the Mfap4 Ϫ/Ϫ mice were expanded to the lung parenchyma.…”
Section: Discussionsupporting
confidence: 70%
“…The mean density of the lungs reported here are similar to those reported by Plathow et al (32) for C57BL/6J female mice of the same age (Ϫ561 HUs) without respiratory gating. Other studies have reported both higher and lower mean densities (2,3,12,24,33,52). The varying values can be explained by the use of the isopressure breath-hold respiratorygating technique for image acquisition, variations in the ages or strains of the animals, or differences in the scaling of images into CT values (10).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Kobayashi et al induced exacerbations using only a single intratracheal administration of LPS (1 mg/kg) to mice with elastase-induced emphysema. Three days after LPS treatment, the authors observed neutrophil infiltration and CD8+ cells in bronchoalveolar lavage fluid (BALF), as well as increased levels of MMP-9 and TIMP-1, whereas after 12 weeks, they found severe alveolar destruction, using the parameter of low-attenuation area percentage (LAA%) on micro-computed X-ray tomography, suggesting intense acute inflammation and severe, irreversible alveolar destruction, respectively [159].…”
Section: Experimental Models Of Copd Exacerbation Lps Infectionmentioning
confidence: 99%